A pre-meal of whey proteins induces differential effects on glucose and lipid metabolism in subjects with the metabolic syndrome: a randomised cross-over trial - Bjørnshave, Ann; Holst, Jens Juul; Hermansen, Kjeld (European journal of nutrition, 2019)
Purpose Postprandial lipaemia (PPL), an independent risk factor for cardiovascular disease, is affected by composition and timing of meals. We evaluated if whey proteins (WP) consumed as a pre-meal before a fat-rich meal reduce postprandial triglyceride (TG) and apolipoprotein B-48 (ApoB-48) responses in subjects with the metabolic syndrome (MeS). Methods An acute, randomised, cross-over trial was conducted. 20 subjects with MeS consumed a pre-meal of 0, 10 or 20 g WP 15 min prior to a fat-rich meal. The responses of TG and ApoB-48 were assessed. We also analysed postprandial responses of free fatty acids (FFA), glucose, insulin, glucagon, glucagon-like peptide 1 (GLP-1), glucose-dependent insulinotropic peptide (GIP) and paracetamol (reflecting gastric emptying rates). Results WP pre-meal did not alter the TG or ApoB-48 responses. In contrast, the insulin response was more pronounced after a pre-meal of 20 g WP than with 10 g WP ( P = 0.0005) and placebo ( P < 0.0001). Likewise, the postprandial glucagon response was greater with a pre-meal of 20 g WP than with 10 g WP ( P < 0.0001) and 0 g WP ( P < 0.0001). A pre-meal with 20 g of WP generated lower glucose ( P = 0.0148) and S-paracetamol responses ( P = 0.0003) and a higher GLP-1 response ( P = 0.0086) than placebo. However, the pre-meal did not influence responses of GIP, FFA or appetite assessed by a Visual Analog Scale. Conclusions Consumption of a WP pre-meal prior to a fat-rich meal did not affect TG and chylomicron responses. In contrast, the WP pre-meal stimulates insulin and glucagon secretion and reduces blood glucose as expected, and delays gastric emptying. Consequently, our study points to a differential impact of a WP pre-meal on lipid and glucose metabolism to a fat-rich meal in subjects with MeS.